The Nineteenth Century - Strunk, Oliver 1901-1980; Solie, Ruth A. (New York Norton, 1998)
Forty-five years after the appearance of the first edition, Oliver Strunk's monumental anthology of writings about music has been thoroughly revised and extended by a team of scholars working under the direction of musicologist Leo Treitler. For this new edition, seven specialists in music history have replaced some selections, added others, contributed new translations, and provided additional notes and introductions. With this series, readers can now acquire a comprehensive picture of Western musical thought and ideas through the ages.
Keywords: 19th Century (1801-1900); Music history; Music theory; Music philosophy and esthetics